The antimicrobial activity and phytochemistry of african wormwood ( artemisia ) - Gwebu, Lehlohonolo, Tebogo (My University, 2003)
Artemisia afra Jacq. wild also known as African wormwood, " umhlonyane" ( Xhosa and Zulu ) "lengana" ( Sotho And Tswana ) and "wildeals" ( Afrikaans 0 is an aromatic shrub belonging to the Asteraceace. It is widespread in South Africa extending from the mountainous regions of South Western cape, along the eastern coast to the Northern Province ( van Wyk et. al;1997 ) Due to the popular use of A. afra. The aerial part of sixteen samples from four natural populations were hydrodistilled and the essential oil analysed by GC_MS and tested for antimicrobial activity on anumber of bacteria and fungi.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Science In Medicine ( Pharmaceutical Affairs )
Keywords: Anti-Infective Agents; Plants; Artemisia